A Combined Model to Examine Contributory Factors to Vietnamese Employee’s Adoption of Life Insurance with Pension Scheme - Hung, Nguyen Thanh; Anh, Tran Thi Xuan; Thu, Tran Thanh (Business and Economic Research, 2024)
This paper combined demographic and psychological variables to construct a model of factors influencing Vietnamese employees' adoption of pension scheme insurance. We surveyed the sample 320 long-term working Vietnamese employees to test the significance of seven exploratory variables on the probability of buying a retirement package: Marital status, Age, Educational Level, Income, Location, Attitude toward pension scheme adoption, and Retirement Financial Need. We ran a binary logistics and found the significant positive impact of these above factors on the pension insurance adoption of Vietnamese employees. Like other developing countries, the financial pressure on the state budget of Vietnam became severe when the expansion of the aging population increased dramatically recently. Hence, the findings of this study provide an essential basis for the Vietnamese government, insurance companies, and agents to accelerate pension product adoption together with ensuring social wealth and financial security for older people in the future